2017
DOI: 10.1128/jcm.00868-17
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry for Use with Positive Blood Cultures: Methodology, Performance, and Optimization

Abstract: Early initiation of effective antibiotics for septic patients is essential for patient survival. Matrix-assisted desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has revolutionized clinical microbiology for isolate identification and has the possibility to impact how blood culture testing is performed. This review discusses the various uses of MALDI-TOF MS for the identification and susceptibility testing of positive blood cultures, the performance of these methods, and the outcomes involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 56 publications
6
73
0
9
Order By: Relevance
“…Although the underlying reason for this discrepancy is not known, it is reasonable to suggest that the bacterial cell wall components may play a role. In line with several previously published studies, the present study shows that all three separation methods have higher performance in identification of Gram-negative bacteria compared with Gram-positive bacteria [21][22][23]. Among the bacteria that could not be identified by the three methods analysed, the two groups, staphylococci and streptococci, dominated.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Although the underlying reason for this discrepancy is not known, it is reasonable to suggest that the bacterial cell wall components may play a role. In line with several previously published studies, the present study shows that all three separation methods have higher performance in identification of Gram-negative bacteria compared with Gram-positive bacteria [21][22][23]. Among the bacteria that could not be identified by the three methods analysed, the two groups, staphylococci and streptococci, dominated.…”
Section: Discussionsupporting
confidence: 90%
“…Almost all the previously published studies have showed that the identification of Gram-negative bacteria is more successful than Gram-positive bacteria by direct MALDI-TOF MS from blood cultures [21][22][23]. Although the underlying reason for this discrepancy is not known, it is reasonable to suggest that the bacterial cell wall components may play a role.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations